Regency England : the age of Lord Liverpool - Plowright, John, 1956- (Lancaster pamphlets., 1996)
The early nineteenth century was marked by public disorder, governmental repression and correction. It was a period of revolution, reaction and reform. This pamphlet focuses on three key issues:* the factors which combined to produce the turmoil and uprisings of 1812-21 and the severity with which they were put down* the validity of the distinction between 'repressive' and 'liberal' phases of the administration* the ability of Lord Liverpool as Prime Minister.